PENGARUH TERAPI REBUSAN DAUN PANDAN WANGI (PANDANUS AMARYLLIFOLIUS) TERHADAP KADAR GULA DARAH PENDERITA DIABETES MELITUS DI DESA NGASEM, KECAMATAN NGASEM, KABUPATEN KEDIRI - Nurfitri, Yuyun; Nur Rahayu, Kun ika; sulistiyoningsuharto, Idola perdana (Jurnal Mahasiswa Kesehatan, 2019)
Diabetes mellitus is a disease characterized by hyperglicemia. High digit incident patient diabetes mellitus in Kediri district 16.760 cases. The research purpose was to know the effect giving boil fragrant pandan leaves (pandanus amaryllifolius) about degree of blood incident patient diabetes mellitus. Design research quasy experiment pre-post control group design. Sample in this research control group is 16 respondents and intervention group is 16 respondents which tacked use technique purposive sampling. Control group just given boil water, the intervention group given boil fragrant pandan leaves. The data was analyzed by Wilcoxon test and then continued to Mann-Whitney test. Based test wilcoxon getting p-value of control group before and after therapy is 0,173 from α (0,05), and p-value intervention group is 0,001 from α (0,05) with mean’s H1 accepted there is effect giving boil fragrant pandan leaves to decrease degree in the blood. Based test Mann-whitney getting p value of control group and intervention group after therapy is 0,000 from α (0,05) with mean’s there is a difference in blood sugar levels after giving boil fragrant pandan leaves control group and intervention group. The conclusion of this research was giving boil fragrant pandan leaves can decrease degree sugar in blood. Hopefully with the research patient diabetic mellitus get know benefit boil of fragrant pandan leaves, so get consume boil fragrant pandan leaves in a routine during 1 month. Key Words: Water boil  of fragrant pandan leaves, Degree sugar in the blood, Diabetic mellitus.